Art As The Parasitic Process of Thought: Art-Work, Art- Labour, and Art-Action in Hannah Arendt - Lewicki, Riley (HannahArendt.net, 2025)
This paper engages in a reading of Hannah Arendt’s consideration of the concept of art in relation to the three central aspects of the vita activa: labour, work, and action. The central argument is that Arendt miscategorises art as work, whereas it is a process of thought. There appears a tension in Arendt’s conception of art, or perhaps more accurately by her placement of art under the domain of work. Work relates to labour as use objects, and to action as art. However, this muddles a concept of work and its place in the world, hampering the “disclosing quality” of words valorized by Arendt. This fraught conjuncture is smoothed if we distinguish the process by which something becomes a use object from the process by which art is created. Thus, I examine the differences Arendt draws between art and use objects, and between what Arendt calls artwork and the wider scope of what is called art within contemporary society. Through this process of comparison, Arendt collapsed the process of fabrication and the two processes which create art: that of judgement and that of art, leading to an unnecessary restriction within her own theory, as it leaves implicit the idea of art as a process itself. Despite its lack of articulation, this idea of art as a process is inherent to her own conception of art. It renders artwork only one form of art and reveals the possibility of art-labour and art-action. Art is not missing from Arendt’s work. It is only muddled. She writes that the process of writing a modern novel is a process of artistic invention. Likewise, Arendt despairs of those who fabricate or manufacture books. If art is fabricated, and books are works of art, as she claims in The Human Condition, then it is meaningless to say that they are no longer written but fabricated, for to write is to fabricate. Thus, we can read her as conceiving of art as a distinct activity. I argue that it is a parasitic activity, one which corrupts the pure forms of activity, that of labour, work, and action, and renders their output and purpose as something “useless”.